Etnomatematika dalam Perancangan Arsitektur Masjid: Integrasi Seni Geometri Islami Dalam Arsitektur Mesjid Harun Keuchik Leumik Banda Aceh - Safwan; Zulfikar Taqiuddin; Mirza; Siti Zulfa Yuzni (Jurnal Serambi Engineering, 2024)
The Harun Keuchik Leumik Mosque, popularly known as the Golden Mosque of Aceh, is a stunning architectural masterpiece that harmoniously blends art, mathematics, and Islamic architecture. Located in Gampong Lamseupeung, Lueng Bata, Banda Aceh, the mosque is a popular destination for both domestic and international visitors. This research aims to delve into the symbolic meaning and aesthetic value embedded in the facade ornaments of the mosque, particularly in relation to the concept of ethnomathematics. Through a qualitative approach, this study describes how mathematical concepts such as geometry, symmetry, and proportion are manifested in the ornaments and structure of the building. Data was collected through interviews, literature review, and direct observation at the research site. The findings reveal a strong correlation between mathematical concepts and the architecture of the Harun Keuchik Leumik Mosque. Various geometric shapes, such as triangles, circles, and cubes, were found to not only serve a structural function but also carry symbolic meanings and aesthetic values that reflect local culture and the fusion of Middle Eastern culture. These findings have significant implications for education, especially in the fields of architecture and mathematics.